PERKEMBANGAN SISTEM MONETER INTERNASIONAL DARI STANDAR EMAS KE BRETTON WOODS HINGGA ERA NILAI TUKAR MENGAMBANG - Risma Enjeli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the development of the international monetary system, starting from the Gold Standard, Bretton Woods, to the floating exchange rate system, which shows complex dynamics and significant influence on global trade and economic stability. The Gold Standard provided exchange rate stability but collapsed due to World War I. The Bretton Woods system then brought a period of stability with fixed exchange rates, but failed due to political and economic instability. Since 1973, the floating exchange rate system has provided flexibility in determining exchange rates, but has also increased vulnerability to market fluctuations and speculation. This study emphasizes the importance of understanding the development of the international monetary system to help countries formulate flexible economic policies, responsive to changing global conditions, and able to face future economic challenges.